Pengolahan Limbah Cair Batik Banten secara Koagulasi Menggunakan Tawas dan Adsorpsi dengan Memanfaatkan Zeolit Alam Bayah - fitriyah Fitriyah; Tauny Akbari; Irfan Alfandiana (Fakultas Teknik, 2022)
The batik industry produces liquid waste from the coloring, washing and rinsing processes. This study was aimed to analyze the quality of Banten batik effluent before and after treatment. The processing is carried out using an experimental method with a batch system by coagulation using alum and adsorption using Bayah's natural zeolite by performing 3 variations of coagulant mass and adsorbent for the dye test parameters, TDS and TSS. The results of the test before treatment were the results for dyes of 344 TCU, TDS 620 mg/L, and TSS 218.5 mg/L. Based on the coagulation treatment using alum, the most efficient coagulant results were obtained to reduce the levels of dyestuffs and TDS, namely by using alum coagulant as much as 1500 mg/L which resulted in 96.6 TCU and 330.0 mg/L respectively, then to reduce TSS levels obtained an efficient coagulant that is 500 mg/L with a yield of 10 mg/L. The adsorption treatment using Bayah natural zeolite can reduce the levels of TDS and TSS with the most efficient results using an adsorbent of 150 g/L obtained for TDS 189.3 mg/L and TSS 13.3 mg/L. So based on the results of processing using coagulation and adsorption methods, it is hoped that the batik industry can apply it in processing the liquid waste produced.